New comparative clinical and biometric findings between acute primary angle-closure and glaucomatous eyes with narrow angle - Mérula,Rafael Vidal (2010)
Purpose: To compare, clinically and biometrically, affected and fellow acute primary angle-closure (APAC) eyes and glaucomatous eyes with narrow angle (NA). Methods: Comparative case series; 30 patients with APAC and 27 glaucomatous patients with NA were evaluated. Keratometry (K), central corneal thickness (CCT), lens thickness (LT), axial length (AL) and anterior chamber depth (ACD) were measured. Parameters defined as lens posisiton (LP) and relative lens position (RLP) were calculated. Results: Biometric difference between APAC-affected and fellow eyes was found only in LP (P=0.046). When fellow eyes were compared to glaucomatous eyes with NA, differences were found in ACD (P=0.009), AL (P=0.010), and LT/AL (P=0.005). The comparison between APAC-affected and glaucomatous eyes with NA showed significant differences in almost all biometric parameters, except for LT (P=0.148) and RLP (P=0.374). We found that the logistic regression model (LRM), built with three parameters (K, CCT and LT/AL), higher than 0.334 could be a reasonable instrument to differentiate APAC eyes from glaucomatous eyes with NA. Conclusions: This study showed that APAC-affected and fellow eyes have similar biometric features, and glaucomatous eyes with NA have a less crowded anterior segment. The LRM built showed promising results in distinguishing APAC from glaucomatous eyes with NA.